Insights into neurological dysfunction of critically ill COVID-19 patients. (February 2021) - Deana, Cristian; Verriello, Lorenzo; Pauletto, Giada; Corradi, Francesco; Forfori, Francesco; Cammarota, Gianmaria; Bignami, Elena; Vetrugno, Luigi; Bove, Tiziana
Abstract: Novel coronavirus spread rapidly around the world infecting millions of people. It was thus declared a pandemic. This new virus damages the lungs. In the most severe cases, it leads to acute respiratory failure that requires intensive care treatment. However, many clinical reports have listed different neurological symptoms, leading to increased interest in the neurological involvement of COVID-19. Various pathophysiological mechanisms have been proposed to explain these neurological aspects. Direct viral invasion of the nervous system, systemic cytokine storm and severe hypoxemia are key factors in the development of symptoms. Critically ill patients present several additional risk factors for nervous system damage. Reasons for these include deep sedation and extended muscular paralysis, bed rest for several days, and the inability to receive proper physical rehabilitation. After ICU treatment, COVID-19 patients generally require an extensive rehabilitation program. However, distancing restrictions mean that in many cases physiotherapists are unable to enter ICUs, delaying the process of rehabilitation. The role of telemedicine should be considered as an adjunctive tool in the rehabilitation of critically ill COVID-19 patients.